Hepatocyte growth control by SOCS1 and SOCS3. (September 2019) - Khan, Md Gulam Musawwir; Ghosh, Amit; Variya, Bhavesh; Santharam, Madanraj Appiya; Kandhi, Rajani; Ramanathan, Sheela; Ilangumaran, Subburaj
Graphical abstract: Highlights: SOCS1 and SOCS3 are indispensable tumor suppressor proteins in hepatocytes. Loss of SOCS1 or SOCS3 accelerates liver regeneration but does not affect hepatostat. SOCS1 regulates HGF signaling whereas SOCS3 controls IL-6 and EGFR signaling. SOCS1 and SOCS3 also modulate the tumor suppressors TP53 and CDKN1A. Abstract: The extraordinary capacity of the liver to regenerate following injury is dependent on coordinated and regulated actions of cytokines and growth factors. Whereas hepatocyte growth factor (HGF) and epidermal growth factor (EGF) are direct mitogens to hepatocytes, inflammatory cytokines such as TNFα and IL-6 also play essential roles in the liver regeneration process. These cytokines and growth factors activate different signaling pathways in a sequential manner to elicit hepatocyte proliferation. The kinetics and magnitude of these hepatocyte-activating stimuli are tightly regulated to ensure restoration of a functional liver mass without causing uncontrolled cell proliferation. Hepatocyte proliferation can become deregulated under conditions of chronic inflammation, leading to accumulation of genetic aberrations and eventual neoplastic transformation. Among the control mechanisms that regulate hepatocyte proliferation, negative feedback inhibition by the 'suppressor of cytokine signaling (SOCS)' family proteins SOCS1 and SOCS3 play crucial roles in attenuating cytokine and growth factor signaling. Loss of SOCS1 or SOCS3 in the mouse liver increases the rate of liver regeneration and renders hepatocytes susceptible to neoplastic transformation. The frequent epigenetic repression of the SOCS1 and SOCS3 genes in hepatocellular carcinoma has stimulated research in understanding the growth regulatory mechanisms of SOCS1 and SOCS3 in hepatocytes. Whereas SOCS3 is implicated in regulating JAK-STAT signaling induced by IL-6 and attenuating EGFR signaling, SOCS1 is crucial for the regulation of HGF signaling. These two proteins also module the functions of certain key proteins that control the cell cycle. In this review, we discuss the current understanding of the functions of SOCS1 and SOCS3 in controlling hepatocyte proliferation, and its implications to liver health and disease.